KLCC Tourism Chatbot based on Chatterbot and FlowXO Frameworks - Tri Basuki, Kurniawan; Mohd Zaki, Zakaria; Misinem, .; Ainaa Izzati, Mohd Nasarudin (INTI International University, 2022)
This research aims to solve the constant problem of any tourist spot, which is information. Whenever tourists would like to travel, they would research many websites and maybe download many mobile applications for everything they would need when travelling. Therefore, a chatbot that helps tourists get the information they want has been developed to solve this problem. Firstly, research was done to gain more knowledge on how Chatbot is created and what suitable technique. Research is also done to achieve information on KLCC. This Chatbot is developed using natural language processing. Natural language processing will be allowed more dynamic input from the user and only needs to detect the keyword in the user input section. The Chatbot can respond to them. This study tested two different approaches to building a chatbot. The Chatbot in this study is developed based on the Python library Chatterbot and Flow XO frameworks. The experiment and testing are conducted with ten people using the Chatbot. The results show that Chatbot can give a response goodly.